Problemática de los Agroquímicos en las plantaciones de Cacao (Theobroma cacao L.) de Ecuador - Sánchez Justillo, Jennifer Mariana (2022)
This document details the Problem of Agrochemicals in Cocoa (Theobroma cacao L.) plantations in Ecuador, referring to the fact that in our country, cocoa cultivation and its production is strongly affected by limiting factors such as traditional growers not contemporary with modern agricultural practices, a variable climate due to “global warming, old crops, susceptible varieties, and a high presence of pests and diseases specific to this type of crop. Regarding the methods of prevention and control of insects and diseases, prevention is not carried out, but there is a high use of chemical control, with the consequent environmental damage and the health of producers and field workers. In addition, there are few who are aware of this situation, carry out mechanical, biological, and/or integrated insect and disease control activities. Together, it is necessary to recommend to cocoa producers that before using control methodologies for insects and diseases, identify the possible insect and fungal pests that could exist in the cocoa plantation, determine the economic impact of possible damage, and define the methods of prevention and control, including: cultural, mechanical, biological control and, as a last resort, chemical control and/or integrated control of pests and diseases, and carry out other educational or experimental research work on this broad subject of pest and disease control in the cocoa cultivation in Ecuador.